Interaksi Sosial Siswa Atas Lingkungan Sekolah di SDN 2 Sidoharjo - Yunita; Ahmad Taufik; Nurlila Kamsi (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
The success of the influence of the school environment in the process of various social actions of several students. The purpose of this research is to use an appropriate description of the basic functions of the school environment in the formation of behavior according to the social demands of students. The location of the research occurred at Public Elementary School (SDN) 2 Sidoharjo, Tugumulyo District, Musi Rawas Regency. The method used in research is an incident or case study. Data collection techniques derived from observation, in-depth interviews and documentation tools, with good informants coming from students, teachers and local community leaders who were determined by purposive sampling. In this study, Bourdieu's theory of habitus and arena is used, in which the habitus is assessed by all activities in the school and the arena is the frequency of the school environment. The results showed that students' social actions were evident in all forms of activities carried out by students in certain social situations. A student's social awareness will be formed by various factors, it could be the reason for external factors or internal factors, meaning that one's actions will continue to be able to adapt to various social situations. The function of the involvement of the school environment in students' social actions, for example: exemplary, habituation, advice, control mechanisms, sanctioning systematic sustainability. Elements of society as one of the applications of all social behavior of many students become an inseparable part and play a role as control of the scale of social priorities in order to become good students.